Adat the legacy of Minangkabau - Rais Yatim Tan Sri Dato' Seri Utama 1942- (Yayasan Warisanegara, 2015)
The exodus towards common law has been overwhelming since the 1874 Treaty of Pangkor and the following British rule in the Malay States and thenceforth from merdeka till now. The duality and alternative legal parameter provided by the Syariah system gives Muslims their own laws in the various states in Malaysia. But where are the adat laws and ways of old for the Malays so as to fulfill at least the requisition of Art, 160 of the Federal Constitution? This is the guiding provision that spells adat as a component ingredient in being a Malay. Where can the Malays go for cultural guidance if not to seek out their own local wisdom under the canopy of adat? The above is partly raised as issues in this important work on adat in Nergeri Sembilan as a phenomenal socio-cultural legacy from Minangkabau of old, one of the major birthplaces of Malay custom apart from Makassar, Java and Acheh? This book also traces the origins, legends and sources of adata, the original Minangkabau philosophy of virtues which later were housed under the adat Perpatih and Temenggung schemes. Ancient wisdoms by way of the pepatah-petitih, perbilangan, peribahasa, pantun, toambo and its other myriah channels and sources are given their inherent interpretations. The book renders justice to Sanskirt, old Malayu, Indian culture and animism. Budi or the Malay concept of virtue is amply elucidated apart from the contributions of Srivijaya, Dharmasraya, Javanese hegemony of old and Minangkabau stalwart influence for the Negeri Sembilan Malays. Reading this work will float the query - where have all the local Malay wisdoms gone?